(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Koroban O. V. Perspective directions of the use of information and communication Technologies are in an educational process. In the article the basic tendencies of informatization of educational industry are outlined in modern terms. The basic requirements of personality are represented in the development. Basic perspective directions of developments and use of facilities of ІКТ are considered.